Cover Feature: Synthetic Fuels from Biomass: Photocatalytic Hydrodecarboxylation of Octanoic Acid by Ni Nanoparticles Deposited on TiO2 (ChemSusChem 2/2022). Issue 2 (27th December 2021) - Du, Xiangze; Peng, Yong; Albero, Josep; Li, Dan; Hu, Changwei; García, Hermenegildo
Abstract : The Cover Feature shows how octanoic acid could be efficiently hydrogenated to n ‐heptane and tetradecane with total selectivity of >80% under the action of UV/Vis light irradiation on Ni/TiO2 catalyst. More information can be found in the Full Paper by X. Du et al .